Phytogenic Feed Additives as an Alternative to Antibiotic Growth Promoters in Broiler Chickens - Murugesan, Ganapathi Raj; Syed, Basharat; Haldar, Sudipto; Pender, Chasity (Frontiers in Veterinary Science, 2015)
The recent trend toward reduction of antibiotic growth promoters (AGP) in North American poultry diets has put tremendous pressure on the industry to look for viable alternatives. In this context, phytogenic feed additives (PFA) are researched to improve gut health and thereby performance. An experiment was conducted with the objective to evaluate the effects of PFA as an alternative to AGP on small intestinal histomorphology, cecal microbiota composition, nutrient digestibility, and growth performance in broiler chickens. A total of 432, day-old Vencobb 400 broiler chicks were randomly assigned to one of three dietary groups, each consisting of 12 replicate pens (n = 12 chicks/pen). The chicks were fed a corn-soybean meal based control (CON), CON + 500 mg/kg of AGP (bacitracin methylene disalicylate containing 450 mg active BMD/g), or CON + 150 mg/kg of proprietary blend of PFA (Digestarom® Poultry) until 39 days of age when samples were collected. Birds fed either AGP or PFA had increased villus height in all three segments of the small intestine in comparison to the birds fed CON (P ≤ 0.05). Furthermore, the PFA fed birds had significantly increased villus height and lower crypt depth compared to AGP fed birds (P ≤ 0.05). Birds fed either additive also had increased total tract digestibility of dry matter, crude protein and ether extract (P ≤ 0.05). The strong effect of the PFA on villus height in the jejunum may suggest augmented nutrient absorption in PFA fed birds. Although both additives reduced total cecal counts of anaerobic bacteria and Clostridium spp., PFA alone reduced the total coliform count while increasing the Lactobacillus spp. count (P ≤ 0.05). These results suggest the establishment of beneficial microbial colonies in PFA fed birds. Overall both PFA and AGP increased body weight gain while lowering the feed conversion ratio (P ≤ 0.05). Hence data from this experiment demonstrate the efficacy of PFA as a substitute to AGP in poultry diets.